SPORT AS A MEANS OF INCLUSION AND INTEGRATION FOR "THOSE OF US WITH DISABILITIES" - Irene Kamberidou; Bonias, Alexandros; Patsantaras, Nikolaos (European Journal of Physical Education and Sport Science, 2019)
Can sport provide a platform for disability awareness as regards both social and biological dimensions? How can sport serve as a tool or means of social inclusion for persons or athletes with disabilities? To address these questions our qualitative study begins with a review of current research on the social dimensions of disability, namely  diverse forms of social exclusion experienced by "those of us with disabilities" (McCall, 2016), such as attitudinal, institutional and environmental barriers, subsequently followed by a case study in Greece. Initially, we discuss today’s shift to inclusion—which advocates a more inclusive and people-first perspective as well as a more empowering language—and distinguish between two concepts/approaches, integration and inclusion, mainly through educational schemes, so as to facilitate the analysis that follows on sport’s role in eliminating social and institutional barriers and promoting inclusion. Inclusive education is a central objective of the UN Convention on the Rights of Persons with Disabilities (CRPD), and other UN and UNESCO initiatives. In this context researchers have been examining sport and physical education as tools, instruments or means of social inclusion and/or integration. Accordingly, to determine whether—and to what extent—sport participation contributes to the inclusion and integration of people with physical disabilities, interviews were conducted with 20 athletes in Athens: semi-structured interviews with 14 male and 6 female Paralympic and World Champions. The findings confirm that both genders confront many forms of social exclusion (attitudinal, environmental and institutional), however their sport participation plays a significant and positive role in their lives. All 20 acknowledge or report sport gives them a social identity, a sport identity and a meaning in life, in addition to contributing to their social integration/inclusion. Conclusions: The lack of disability awareness, information and knowledge accounts for many of the barriers. Recognizing both the social and biological dimensions of disability is important. The disability community needs visibility, i.e. coverage in mainstream media to cultivate inclusion, promote and reproduce role models and mentors, along with a wider disability awareness campaign, in which sport could play a vital role in changing stereotypes and attitudes, in addition to eliminating the supercrip identity.   Keywords: integration, inclusion, inclusive education, physical disability, supercrip identity, sport identity, social exclusion, empowering language-terminology, mainstream media